Hinge Strut: A New Septal Strut for Nasal Tip Projection, Definition, and Stability in Latino Noses - Wilder A. Pérez Willis, MD; Gerardo A. Adrianzen Nuñez, MD; Cynthia P. Mendoza Guerra, MD; Wilder A. Perez Soto, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Obtaining ideal support to maintain the nasal tip has been investigated in several rhinoplasty studies. We aimed to describe a support technique, namely the use of a “hinge strut” (HS) for the nasal tip in Latino noses and to evaluate nasolabial angles at 6-months follow-up. Methods:. In total, 46 Latino patients who had undergone rhinoplasty using the HS technique between June 2021 and June 2022 were recruited in Lima, Peru. All patients had nasolabial angle measurements taken preoperatively and at 1, 3, and 6 months postoperatively in active and passive positions to evaluate angle changes during this 6-month period. Results:. We evaluated 38 women and six men aged 18–45 years (mean age, 25.74 years). In the passive position, the mean nasolabial angles were 91.5 degrees preoperatively and 106, 104, and 103 degrees at 1, 3, and 6 months, respectively, postoperatively. In the active position, the mean nasolabial angles were 85.5 degrees preoperatively and 102.6, 99.1, and 98.1 degrees at 1, 3, and 6 months, respectively, postoperatively (P < 0.0001, using Friedman chi-square test). Conclusions:. The HS technique is safe and reproducible, with nasal tip maintenance and an adequate angle elevation trend observed at 6-months follow-up. Further studies and longer observation times are necessary to determine longer-term outcomes.